Insulating paste for solar cell and preparation method of insulating paste

By introducing silicone modified nanopowders into epoxy resin insulating glues, a coating structure with in-situ hybridization of epoxy/silicon/nano powders is formed, the existing insulating glues have poor high temperature resistance and serious shrinkage in BC solar cells are solved, and the insulating glue with high temperature resistance, high hardness and low shrinkage rate is achieved, meeting the humidity and heat resistance requirements of photovoltaic silicon wafers.

CN119823694APending Publication Date: 2025-04-15HEYU RENEWABLE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411888996.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing epoxy resin insulating glue has poor high temperature resistance in BC solar cells, is prone to softening and deformation, causes leakage, severe contraction after curing, and is difficult to meet the humidity and heat resistance requirements of photovoltaic silicon wafers.

Method used

Silicone modified nanopowder is introduced into epoxy resin insulating glue, and the active groups of multiple amino groups or epoxy groups participate in the cross-linking and curing of epoxy resins to form an in-situ hybrid coating structure, thereby improving the mechanical properties and moisture and heat resistance of the insulating glue.

Benefits of technology

It significantly improves the high temperature resistance, pencil hardness, adhesion, low shrinkage and humidity resistance of the insulating adhesive, ensuring that there is no leakage during the welding process, and maintains stable bonding strength and weather resistance in outdoor environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200131840000031
    Figure BDA0005200131840000031
  • Figure BDA0005200131840000032
    Figure BDA0005200131840000032
  • Figure BDA0005200131840000033
    Figure BDA0005200131840000033
Patent Text Reader

Abstract

The invention provides insulating glue for a solar cell and a preparation method thereof. The insulating glue for the solar cell comprises a component A with epoxy resin as a main component and a component B with a curing agent as a main component, wherein the component A and / or the component B further comprise organic silicon modified nano powder, and organic silicon comprises a plurality of amino or epoxy active groups. According to the insulation paste for the solar cell and the preparation method of the insulation paste, provided by the invention, the organic silicon modified nano powder which can participate in epoxy curing and provides an epoxy curing coating with excellent toughness, hardness and high temperature resistance is introduced into the epoxy resin insulation paste; therefore, the insulating glue with high temperature resistance, high pencil hardness, high adhesive force, low shrinkage rate and heat and humidity resistance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of insulating adhesives, and in particular to an insulating adhesive for solar cells and a preparation method thereof. Background Art

[0002] BC (back contact) solar cells, full name back contact solar cells, have become the mainstream direction of the new generation of solar cell technology due to their higher photoelectric conversion efficiency compared to conventional solar cells. The positive and negative fine grid lines of BC solar cells are arranged in a forked shape on the back of the cell, the main grid line and the auxiliary fine grid line are printed vertically, the connection between the positive main grid segment and the negative fine grid line is isolated by printing insulating glue, and the connection between the negative main grid segment and the positive fine grid line is isolated by printing insulating glue.

[0003] At present, BC solar cells often use epoxy resin insulating glue, which is mostly a reactive ink or composition prepared with epoxy resin, active diluent, initiator, and additives as raw materials. Because it evolved from the solder mask ink in the circuit board manufacturing industry, its applicability is limited. Epoxy resin has poor high temperature resistance and is easily softened and deformed during the welding process, resulting in leakage, which causes the solar cell to short-circuit; in addition, epoxy resin shrinks severely after curing, resulting in a large warping height of the printed solar cell, affecting the yield of photovoltaic modules during the preparation process; in addition, photovoltaic solar cells require higher moisture and heat resistance, but photovoltaic silicon wafers are difficult to adhere to the substrate, so the existing epoxy resin insulating glue is difficult to meet the requirements of BC solar cells. Summary of the invention

[0004] Based on the technical problems existing in the background technology, the present invention proposes an insulating adhesive for solar cells and a preparation method thereof, by introducing silicone-modified nanopowders into epoxy resin insulating adhesives that can participate in epoxy curing and provide excellent toughness, hardness and high temperature resistance of the epoxy cured coating, thereby obtaining an insulating adhesive with high temperature resistance, high pencil hardness, high adhesion, low shrinkage and moisture and heat resistance.

[0005] The present invention provides an insulating adhesive for solar cells, comprising a component A whose main component is epoxy resin and a component B whose main component is a curing agent;

[0006] Wherein, component A and / or component B also include organosilicon-modified nanopowder, wherein the organosilicon contains a plurality of amino or epoxy active groups.

[0007] In the present invention, epoxy resin, curing agent and organosilicon modified nano powder are blended, and multiple amino or epoxy active groups contained in the organosilicon modified nano powder are utilized to participate in the cross-linking and curing of epoxy resin, thereby forming an epoxy / organosilicon / nanopowder in-situ hybrid coating structure. This coating structure is essentially a three-dimensional network structure cross-linked structure, which can greatly increase the dispersion ability of nano powder in the insulating adhesive system, improve the dispersion state of nano powder in the epoxy resin matrix, and prevent the nano powder from agglomerating and failing to function. On the other hand, it can improve the mechanical properties of the corresponding coating after the obtained insulating adhesive is cured and the bonding strength on different substrates, and impart excellent physical and mechanical properties, moisture and heat resistance and electrical insulation properties.

[0008] Preferably, the organosilicon-modified nanopowder is obtained by grafting nanopowder with a silane coupling agent and polyaminoorganosilane or polyepoxyorganosilane, wherein the silane coupling agent contains an active group that can react with an amino group or an epoxy group.

[0009] Preferably, the silane coupling agent is an amino-containing silane coupling agent or an epoxy-containing silane coupling agent;

[0010] Preferably, the amino-containing silane coupling agent is at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldiethoxysilane, N-phenylaminomethyltriethoxysilane, N-phenylaminomethyltrimethoxysilane or 3-(2-aminoethyl)-aminopropyltriethoxysilane;

[0011] Preferably, the epoxy-containing silane coupling agent is at least one of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane or β-(3,4-epoxycyclohexyl)-ethyltriethoxysilane.

[0012] Preferably, the polyaminoorganosilane is at least one of aminopropylcyclotetrasiloxane, bisaminopropyl polydimethylsiloxane or amino caged polysilsesquioxane;

[0013] Preferably, the polyepoxy organosilane is at least one of diglycidyloxypropyltetramethyldisiloxane, epoxycyclohexylcyclotetrasiloxane, glycidyloxypropylcyclotetrasiloxane, glycidyloxypropyl dicapped polydimethylsiloxane or glycidyloxypropyl caged polysilsesquioxane.

[0014] The structural formula of aminopropylcyclotetrasiloxane is shown below:

[0015]

[0016] The structural formula of bis-aminopropyl polydimethylsiloxane is as follows:

[0017]

[0018] The structural formula of amino cage polysilsesquioxane is as follows:

[0019]

[0020] R is an aminoalkyl group;

[0021] The structural formula of diglycidyloxypropyltetramethyldisiloxane is shown below:

[0022]

[0023] The structural formula of glycidyloxypropylcyclotetrasiloxane is shown below:

[0024]

[0025] The structural formula of glycidyl ether oxypropyl di-terminated polydimethylsiloxane is as follows:

[0026]

[0027] The structural formula of glycidyl ether oxypropyl cage polysilsesquioxane is as follows:

[0028]

[0029] In the specific preparation process of the present invention, the nano powder is subjected to coupling reaction with a silane coupling agent containing active reaction sites to obtain the nano powder grafted with the silane coupling agent; the nano powder grafted with the silane coupling agent is then subjected to grafting reaction with a polyamino or polyepoxy organic silane that can react with the active reaction sites to obtain the organic silicon modified nano powder;

[0030] In the present invention, the nanopowder is surface-modified by a silane coupling agent containing active reaction sites, and certain reactive sites are given to the surface of the nanopowder. Then, polyamino or polyepoxy organic silane is grafted onto the surface of the nanopowder by interfacial reaction to obtain the organosilicon-modified nanopowder.

[0031] Preferably, the nano powder is at least one of silicon dioxide or aluminum oxide;

[0032] Preferably, the amount of the organosilicon-modified nanopowder is 1-50 wt % of the total weight of the A component and the B component.

[0033] Preferably, the epoxy resin is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, novolac epoxy resin or alicyclic epoxy resin; the curing agent is at least one of dicyandiamide, m-phenylenediamine, ethylenediamine, diethylenetriamine, triethylenetetramine, 4,4'-diaminodiphenylmethane, diaminodiphenyl sulfone, phthalic anhydride or hexahydrophthalic anhydride;

[0034] Preferably, the weight ratio of component A to component B is 1:0.8-1.2.

[0035] Preferably, component A and / or component B further comprises a solvent or a filler;

[0036] Preferably, the solvent is at least one of terpineol, dodecane, butyl acetate, turpentine, dibasic acid ester, acetone, toluene, ethyl acetate, ethylene glycol monomethyl ether, ethylene glycol butyl ether, propylene glycol butyl ether, dipropylene glycol monomethyl ether or diethylene glycol butyl ether acetate;

[0037] Preferably, the filler is at least one of silicon powder, glass powder, talc, mica, aluminum nitride, boron nitride, silicon carbide, strontium titanate, barium titanate, barium sulfate, calcium silicate or calcium carbonate.

[0038] Preferably, component A and / or component B also include a functional additive;

[0039] Preferably, the functional auxiliary agent is at least one of a leveling agent, a dispersant, a defoaming agent, a curing accelerator or a thixotropic agent.

[0040] Preferably, the leveling agent is at least one of an acrylic leveling agent or a fluorocarbon leveling agent, the dispersant is at least one of an aminoacrylate copolymer, a phosphate or a polyacid homopolymer; the defoamer is at least one of a silicone defoamer, a polyether defoamer or a mineral oil defoamer; the curing accelerator is an imidazole curing accelerator, preferably at least one of 2-methylimidazole, 1-methylimidazole, 2-ethyl-4-methylimidazole or 1-cyanoethyl-2-ethyl-4-methylimidazole, and the thixotropic agent is at least one of polyamide wax or hydrogenated castor oil.

[0041] The present invention also proposes a method for preparing the above-mentioned insulating adhesive for solar cells, comprising: first separately preparing a component A whose main component is epoxy resin and a component B whose main component is curing agent, and then mixing the component A whose main component is epoxy resin and the component B whose main component is curing agent to obtain the insulating adhesive for solar cells.

[0042] Beneficial effects:

[0043] The insulating adhesive provided by the present invention achieves cross-linking hybridization modification with epoxy resin by surface modification of nano powders. The obtained insulating adhesive not only meets the insulation requirements, but also significantly enhances the mechanical properties and greatly increases its maximum operating temperature. During the welding process of BC solar cells, the obtained insulating adhesive can still provide good protection for the electrodes at high temperatures, and also has excellent comprehensive performance in terms of resistance to moisture and heat aging, and can maintain stable bonding strength and weather resistance in harsh outdoor environments. The coating has a smaller shrinkage rate at an appropriate degree of curing, and can effectively prevent silicon wafer warping caused by film shrinkage. DETAILED DESCRIPTION

[0044] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.

[0045] Example 1

[0046] This embodiment provides an insulating adhesive for solar cells, which is composed of component A and component B, and component A and component B are used in a weight ratio of 1:1.05;

[0047] Wherein, component A includes, by weight: 40 parts of bisphenol A epoxy resin (JER 828), 40 parts of phenolic epoxy resin (DEN431), 40 parts of organosilicon modified nano powder, 10 parts of filler (talc), 10 parts of solvent (ethylene glycol monomethyl ether), 1 part of defoamer (Agitan315), 0.5 parts of thixotropic agent (hydrogenated castor oil); component B includes, by weight: 40 parts of curing agent 1 (dicyandiamide), 40 parts of curing agent 2 (4,4'-diaminodiphenylmethane), 1 part of wetting agent (TEGO 4000), and 1 part of dispersant (EFKA4580);

[0048] The above-mentioned organosilicon modified nano powder is prepared according to the following method:

[0049] Nano-silicon dioxide (average particle size of 50 nm) was added to a mixed solvent consisting of anhydrous ethanol and water in a volume ratio of 4:1, and after ultrasonic dispersion, ammonia water was added to adjust the pH to 9, and then γ-glycidyloxypropyltrimethoxysilane (KH-560) with a mass percentage of 20 wt% of the nano-silicon dioxide was added, and the mixture was stirred at 50° C. for 6 h, and then centrifuged, washed, and dried to obtain KH-560 graft-modified nano-powder;

[0050] The KH-560 grafted modified nanopowder is added to water, and after ultrasonic dispersion, 15 wt% of aminopropyl cyclotetrasiloxane by weight of nano-silicon dioxide is added, and after sufficient stirring and dissolution, the mixture is stirred and reacted at 90° C. for 4 h. After vacuum removal of the solvent, the mixture is dried and ground to obtain the organosilicon-modified nanopowder.

[0051] This embodiment also provides a method for preparing an insulating adhesive for solar cells, comprising the following steps:

[0052] (1) 40 parts by weight of bisphenol A epoxy resin (JER 828) and 40 parts of phenolic epoxy resin (DEN 431) were added to a reactor, stirred and mixed at a speed of 500 r / min for 0.5 h, then 10 parts of solvent (ethylene glycol monomethyl ether), 1 part of defoaming agent (Agitan315), and 0.5 parts of thixotropic agent (hydrogenated castor oil) were added, and the stirring was continued for 0.5 h at the previous speed. Finally, 40 parts of organosilicon-modified nanopowder and 10 parts of filler (talcum powder) were added, and the mixture was stirred for another 2 h at the previous speed. After mixing, vacuum degassing was performed to obtain component A; 40 parts of curing agent 1 (dicyandiamide), 40 parts of curing agent 2 (4,4'-diaminodiphenylmethane), and 0.5 parts of wetting agent (TEGO 4000) 1 part and dispersant (EFKA4580) 1 part were added into the reaction kettle, stirred and mixed at a speed of 500 r / min for 0.5 h, and vacuum degassed to obtain component B;

[0053] (2) The above two components A and B are mixed and stirred evenly at a weight ratio of 1:1.05 to obtain the insulating adhesive for solar cells.

[0054] The insulating adhesive for solar cells can be coated on the solar cell by screen printing within the applicable period, cured at 60° C. for 2 hours, and the performance test can be carried out after stable bonding.

[0055] Example 2

[0056] This embodiment provides an insulating adhesive for solar cells, which is prepared by referring to the method described in Example 1, except that the organosilicon-modified nanopowder is prepared according to the following method:

[0057] Nano-silicon dioxide (average particle size of 50 nm) was added to a mixed solvent consisting of anhydrous ethanol and water in a volume ratio of 4:1, and after ultrasonic dispersion, ammonia water was added to adjust the pH to 9, and then γ-glycidyloxypropyltrimethoxysilane (KH-560) with a mass percentage of 20 wt% of the nano-silicon dioxide was added, and the mixture was stirred at 50° C. for 6 h, and then centrifuged, washed, and dried to obtain KH-560 graft-modified nano-powder;

[0058] The KH-560 grafted modified nanopowder is added to water, and after ultrasonic dispersion, octaaminopropyl cage-shaped polysilsesquioxane with a mass percentage of 15 wt% of nano-silicon dioxide is added, and after sufficient stirring and dissolution, the mixture is stirred and reacted at 90° C. for 4 h. After vacuum removal of the solvent, the mixture is dried and ground to obtain the organosilicon-modified nanopowder.

[0059] Example 3

[0060] This embodiment provides an insulating adhesive for solar cells, which is prepared by referring to the method described in Example 1, except that the organosilicon-modified nanopowder is prepared according to the following method:

[0061] Nano-silicon dioxide (average particle size of 50 nm) was added to a mixed solvent consisting of anhydrous ethanol and water in a volume ratio of 4:1, and after ultrasonic dispersion, ammonia water was added to adjust the pH to 9, and then γ-aminopropyltriethoxysilane (KH-550) with a mass percentage of 20 wt% of the nano-silicon dioxide was added, and the mixture was stirred at 50° C. for 6 h, and then centrifuged, washed, and dried to obtain KH-550 graft-modified nano-powder;

[0062] The KH-550 grafted modified nano powder is added to water, and after ultrasonic dispersion, 15 wt% of diglycidyloxypropyltetramethyldisiloxane by weight of nano silicon dioxide is added, and after sufficient stirring and dissolution, the mixture is stirred and reacted at 90° C. for 4 h. After the solvent is removed in vacuo, the mixture is dried and ground to obtain the organosilicon-modified nano powder.

[0063] Example 4

[0064] This embodiment provides an insulating adhesive for solar cells, which is prepared by referring to the method described in Example 1, except that the organosilicon-modified nanopowder is prepared according to the following method:

[0065] Nano-silicon dioxide (average particle size of 50 nm) was added to a mixed solvent consisting of anhydrous ethanol and water in a volume ratio of 4:1, and after ultrasonic dispersion, ammonia water was added to adjust the pH to 9, and then γ-aminopropyltriethoxysilane (KH-550) with a mass percentage of 20 wt% of the nano-silicon dioxide was added, and the mixture was stirred at 50° C. for 6 h, and then centrifuged, washed, and dried to obtain KH-550 graft-modified nano-powder;

[0066] The KH-550 grafted modified nanopowder is added to water, and after ultrasonic dispersion, 15 wt% of the mass of nano-silicon dioxide glycidyl ether oxypropyl caged polysilsesquioxane is added, and after sufficient stirring and dissolution, the mixture is stirred and reacted at 90° C. for 4 h. After vacuum removal of the solvent, the mixture is dried and ground to obtain the organosilicon-modified nanopowder.

[0067] Comparative Example 1

[0068] This comparative example provides an insulating adhesive for solar cells, which is prepared by referring to the method described in Example 1, except that the organosilicon-modified nanopowder is replaced by nano-silicon dioxide (with an average particle size of 50 nm).

[0069] Comparative Example 2

[0070] This comparative example proposes an insulating adhesive for solar cells, which is prepared by referring to the method described in Example 1, except that the organosilicon-modified nanopowder is prepared according to the following method: nano-silicon dioxide (average particle size of 50 nm) is added to a mixed solvent consisting of anhydrous ethanol and water in a volume ratio of 4:1, and after ultrasonic dispersion, ammonia water is added to adjust the pH to 9, and then γ-glycidyloxypropyltrimethoxysilane (KH-560) with a mass percentage of 20 wt% of the nano-silicon dioxide is added, and the reaction is stirred at 50°C for 6 hours, followed by centrifugation, washing, and drying to obtain a KH-560 grafted modified nanopowder, which is the organosilicon-modified nanopowder.

[0071] Comparative Example 3

[0072] This comparative example proposes an insulating adhesive for solar cells, which is prepared by referring to the method described in Example 1, except that the organosilicon-modified nanopowder is prepared according to the following method: nano-silicon dioxide (average particle size of 50 nm) is added to a mixed solvent consisting of anhydrous ethanol and water in a volume ratio of 4:1, and after ultrasonic dispersion, ammonia water is added to adjust the pH to 9, and then 20 wt% of γ-aminopropyltriethoxysilane (KH-550) by the mass of nano-silicon dioxide is added, and the reaction is stirred at 50°C for 6 hours, followed by centrifugation, washing, and drying to obtain a nano-powder grafted with KH-550, which is the organosilicon-modified nano-powder.

[0073] The insulating adhesives described in the above embodiments and comparative examples were subjected to performance tests, wherein the pencil hardness was tested according to the standard GB / T6739-2006 "Determination of film hardness by pencil method for paints and varnishes"; the volume resistivity was tested according to the standard GB / T 1410 "Test method for volume resistivity and surface resistivity of materials"; the bonding strength was tested according to the standard GB / T 2790 "Test method for 180° peel strength of insulating adhesives - flexible material to rigid material"; the test method for wet heat aging resistance was based on the standard GB / T 2423.3 "High and low temperature wet heat test method", and the yellowing index ( Δ YI) and peel strength, yellowing index ( ΔYI) is measured according to the national standard GB 2409-80 "Plastic Yellow Index Test Method"; the boiling resistance is to immerse the battery cell coated with insulating glue in 100℃ boiling water and observe the time for the coating to shrink or bubble; the low shrinkage test is tested according to the standard GB4677.5-1984 "Printed Circuit Board Warpage Test Method", and is characterized by the height of the protrusion of the battery cell (coating thickness 40±5μm) coated with insulating glue after the insulating glue solidifies and shrinks; the high temperature resistance is to use a 300℃ soldering pen to scratch the coating on the battery cell coated with insulating glue. If the contact is melted, collapsed, melted through or carbonized by the soldering pen, it is considered unqualified, and slight scratches or no damage on the surface are considered qualified.

[0074] Table 1 Performance results of the insulating adhesives described in the examples and comparative examples

[0075]

[0076] Note: The unit of volume resistivity is Ω·m, the unit of bonding strength is N / cm, the unit of water boiling resistance is h, and the unit of low shrinkage is mm.

[0077] It can be seen from Table 1 above that the insulating adhesive of the present invention has high hardness, high electrical insulation performance, high water boiling resistance and high bonding strength, and has a small shrinkage rate at high temperature, less yellowing during wet heat aging, and good bonding strength retention ability.

[0078] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An insulating adhesive for solar cells, characterized in that: It comprises a component A whose main component is epoxy resin and a component B whose main component is curing agent; Wherein, component A and / or component B also include organosilicon-modified nanopowder, wherein the organosilicon contains a plurality of amino or epoxy active groups.

2. The insulating adhesive for solar cells according to claim 1, characterized in that: The organosilicon-modified nano powder is obtained by grafting nano powder with a silane coupling agent and polyamino organic silane or polyepoxy organic silane, wherein the silane coupling agent contains an active group that can react with an amino group or an epoxy group.

3. The insulating adhesive for solar cells according to claim 2, characterized in that: The silane coupling agent is an amino-containing silane coupling agent or an epoxy-containing silane coupling agent; Preferably, the amino-containing silane coupling agent is at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldiethoxysilane, N-phenylaminomethyltriethoxysilane, N-phenylaminomethyltrimethoxysilane or 3-(2-aminoethyl)-aminopropyltriethoxysilane; Preferably, the epoxy-containing silane coupling agent is at least one of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane or β-(3,4-epoxycyclohexyl)-ethyltriethoxysilane.

4. The insulating adhesive for solar cells according to claim 2 or 3, characterized in that: The polyaminoorganosilane is at least one of aminopropylcyclotetrasiloxane, bisaminopropyl polydimethylsiloxane or amino caged polysilsesquioxane; The polyepoxy organosilane is at least one of diglycidyloxypropyltetramethyldisiloxane, epoxycyclohexylcyclotetrasiloxane, glycidyloxypropylcyclotetrasiloxane, glycidyloxypropyl double-terminated polydimethylsiloxane or glycidyloxypropyl caged polysilsesquioxane.

5. The insulating adhesive for solar cells according to any one of claims 1 to 4, characterized in that: The nano powder is at least one of silicon dioxide or aluminum oxide; Preferably, the amount of the organosilicon-modified nanopowder is 1-50 wt % of the total weight of the A component and the B component.

6. The insulating adhesive for solar cells according to any one of claims 1 to 5, characterized in that: The epoxy resin is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, novolac epoxy resin or alicyclic epoxy resin; the curing agent is at least one of dicyandiamide, m-phenylenediamine, ethylenediamine, diethylenetriamine, triethylenetetramine, 4,4'-diaminodiphenylmethane, diaminodiphenyl sulfone, phthalic anhydride or hexahydrophthalic anhydride; Preferably, the weight ratio of component A to component B is 1:0.8-1.

2.

7. The insulating adhesive for solar cells according to any one of claims 1 to 6, characterized in that: Component A and / or component B also include solvents or fillers; Preferably, the solvent is at least one of terpineol, dodecane, butyl acetate, turpentine, dibasic acid ester, acetone, toluene, ethyl acetate, ethylene glycol monomethyl ether, ethylene glycol butyl ether, propylene glycol butyl ether, dipropylene glycol monomethyl ether or diethylene glycol butyl ether acetate; Preferably, the filler is at least one of silicon powder, glass powder, talc, mica, aluminum nitride, boron nitride, silicon carbide, strontium titanate, barium titanate, barium sulfate, calcium silicate or calcium carbonate.

8. The insulating adhesive for solar cells according to any one of claims 1 to 7, characterized in that: Component A and / or component B also include functional additives; Preferably, the functional auxiliary agent is at least one of a leveling agent, a dispersant, a defoaming agent, a curing accelerator or a thixotropic agent.

9. The insulating adhesive for solar cells according to claim 8, characterized in that: The leveling agent is at least one of an acrylic leveling agent or a fluorocarbon leveling agent, the dispersant is at least one of an aminoacrylate copolymer, a phosphate or a polyacid homopolymer; the defoamer is at least one of an organosilicon defoamer, a polyether defoamer or a mineral oil defoamer; the curing accelerator is an imidazole curing accelerator, preferably at least one of 2-methylimidazole, 1-methylimidazole, 2-ethyl-4-methylimidazole or 1-cyanoethyl-2-ethyl-4-methylimidazole, and the thixotropic agent is at least one of polyamide wax, fumed silica or hydrogenated castor oil.

10. A method for preparing the insulating adhesive for solar cells according to any one of claims 1 to 9, characterized in that: include: Firstly, component A whose main component is epoxy resin and component B whose main component is curing agent are prepared respectively, and then component A whose main component is epoxy resin and component B whose main component is curing agent are mixed evenly to obtain the insulating adhesive for solar cells.